The Serendipity Theorem for an Endogenous Open Economy Growth Model - Ziesemer, Thomas (Scientific Research, 2018)
A Samuelsonian serendipity theorem for an endogenous growth model is derived. The formula for optimal population growth rate deviates from those of the model with exogenous population growth rates in a third best endogenous growth model of the Lucas type with imperfect international capital movements and human capital externalities. Calibration shows that the effect of variation of the exogenous population growth rates on other variables and the deviation of population growth rates from its optimal value are small. The reason is that labour supply, interest rates and technical change are endogenous. There is not much of an incentive for population growth policy unless Frisch parameters change with ageing.
Keywords: Open Economy; Endogenous Growth; Human Capital; Serendipity Theorem; Ageing